Prevalence of Post Infectious Glomerulonephritis (PIGN) and Associated Complication - Kalakheti, BalaKrishna; Chaudhary, Brajesh Raj; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Post infectious glomerulonephritis (PIGN) is the most common renal disease in children causing significant morbidity. The affected children present with features of acute nephric syndrome (hematuria, hypertension, edema and oliguria. The objective of this study was to determine the prevalence, clinical characteristics, complications, and outcomes of children presenting with post infectious glomerulonephritis in paediatric ward of tertiary care hospital. Methods This was a prospective observational study conducted at a tertiary care hospital in Chitwan, Nepal from March 1st 2020 to February 28th 2021. Children aged 4 – 15 years satisfying 2 out of 4 features of acute nephritic syndrome were included in the study. After discharge, patients were followed up at 4 weeks and 8 weeks. Data entry was done in statistical packages for the social science version 20. Results Among 63 children recruited with acute nephritic syndrome, 73% had Post infectious glomerulonephritis. The most common etiology of PIGN was Post streptococcal glomerulonephritis (63%). The mean age of children was 11.2 (±3.2) years. Males to females’ ratio was 1.5:1. The most common presenting feature was edema (100%). The most common complication was acute kidney injury (41.3%). Conclusion Post infectious glomerulonephritis was the most common cause of acute nephritic syndrome in children. High incidence of life-threatening complications like CCF, retinopathy, encephalopathy and renal insufficiency occur that require close monitoring and timely intervention to prevent morbidity and mortality.